2015
DOI: 10.1139/bcb-2014-0153
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of phosphoenolpyruvate synthetase (PEPs) and its inhibition by sodium fluoride: potential magnesium and aluminum fluoride complexes of phosphoryl transfer

Abstract: Phosphoenolpyruvate synthase (PEPs) catalyzes the conversion of pyruvate to phosphoenolpyruvate (PEP) using a two-step mechanism invoking a phosphorylated-His intermediate. Formation of PEP is an initial step in gluconeogenesis, and PEPs is essential for growth of Escherichia coli on 3-carbon sources such as pyruvate. The production of PEPs has also been linked to bacterial virulence and antibiotic resistance. As such, PEPs is of interest as a target for antibiotic development, and initial investigations of PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…It has long been known that fluoride ions can interrupt glycolysis by inhibiting the activities of the glycolytic enzyme, enolase ( 6 ) and the gluconeogenetic enzyme, phosphoenolpyruvate synthetase ( 7 ). Experiments on eukaryotic cells have shown that inhibition of these enzymes reduces ATP levels ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been known that fluoride ions can interrupt glycolysis by inhibiting the activities of the glycolytic enzyme, enolase ( 6 ) and the gluconeogenetic enzyme, phosphoenolpyruvate synthetase ( 7 ). Experiments on eukaryotic cells have shown that inhibition of these enzymes reduces ATP levels ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…This metabolic pathway is particularly essential under the anaerobic conditions encountered by E. coli and other pathogenic bacteria in their animal hosts. It has long been known that fluoride ions inhibit the activities both the glycolytic enzyme enolase ( 6 ) and gluconeogenetic enzyme phosphoenolpyruvate synthetase ( 7 ). Enolase is a key glycolytic enzyme involved in converting 2-glycerol phosphate to phosphoenolpyruvate ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of these experiments demonstrated that adding cofactors into the reaction mix that inhibit or activate enzymes and pathways that directly interact with the protein synthesis reaction can improve yields and synthesis duration. The cofactors included: increasing the amount of ATP produced in reaction by adding additional factors to react with pyruvate; increasing the concentration of amino acids in the reaction mix to prevent resource exhaustion; and the inhibition of the futile cycle of PEP synthetase via oxalate addition which prevented conversion of phosphoenolpyruvate product back into pyruvate precursor [35]. Another experiment showed an enzyme-based cell-free platform that exhibited CFPS reactions in two separate formats: using purified components rather than a cell lysate and coupled transcription/translation [15].…”
Section: Cell-free Metabolic Engineeringmentioning
confidence: 99%
“…In the enzymatic mechanism, the enolate of pyruvate is generated within the active site of the enzyme (stabilized by Mg 2+ ), which subsequently undergoes phosphoryl transfer from a phosphohistidine intermediate to yield PEP. [32][33][34] In the following steps of anabolic pathways, PEP provides all carbon and phosphoryl groups for the sugar-phosphate intermediates of gluconeogenesis and the pentose phosphate pathway, including ribose-5phosphate, the building block for ribonucleotide biosynthesis. Thus, enzymatic phosphorylation serves not only a bioenergetic role but also a fundamental structural role in biochemistry through PEP.…”
Section: Introductionmentioning
confidence: 99%